2017
DOI: 10.1111/1744-7917.12475
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma harzianum enhances tomato indirect defense against aphids

Abstract: Many fungal root symbionts of the genus Trichoderma are well-known for their beneficial effects on agronomic performance and protection against plant pathogens; moreover, they may enhance protection from insect pests, by triggering plant resistance mechanisms. Defense barriers against insects are induced by the activation of metabolic pathways involved in the production of defense-related plant compounds, either directly active against herbivore insects, or exerting an indirect effect, by increasing the attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 43 publications
7
46
1
8
Order By: Relevance
“…Very little is known about the effects of endophytic fungi on plant volatile production [mainly focused on Trichoderma species, e.g., Battaglia et al (2013) , Coppola et al (2017) , Contreras-Cornejo et al (2018) ] and to the best of our knowledge, no previous study has ever explored how plant colonization by an endophytic fungus mediates the volatile-regulated attraction of insect predators to spider mite-infested plants. We herein show that the generalist predator M. pygmaeus was attracted to FsK-colonized plants irrespectively of the presence of spider mites (Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is known about the effects of endophytic fungi on plant volatile production [mainly focused on Trichoderma species, e.g., Battaglia et al (2013) , Coppola et al (2017) , Contreras-Cornejo et al (2018) ] and to the best of our knowledge, no previous study has ever explored how plant colonization by an endophytic fungus mediates the volatile-regulated attraction of insect predators to spider mite-infested plants. We herein show that the generalist predator M. pygmaeus was attracted to FsK-colonized plants irrespectively of the presence of spider mites (Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, certain root endophytic fungi have been shown to increase the expression of defense-related genes and the production of secondary metabolites that may be relevant to plant defense ( Pieterse et al, 2014 ). In addition, a few studies involving endophytic fungi have reported negative effects on above ground herbivores thus enhancing their potent role in plant resistance to biotic stressors ( Jallow et al, 2004 ; Jaber and Vidal, 2009 , 2010 ; Muvea et al, 2014 ; Coppola et al, 2017 ; Contreras-Cornejo et al, 2018 ). Nevertheless, our understanding of endophytic fungi – plant – herbivore interactions is still at its infancy thus calling for more empirical studies on the significance of horizontally transmitted endophytes in plant–herbivore interactions ( Gan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Trichoderma ‐induced resistance in plants leads to physiological and biochemical changes including enhanced defence enzymatic activity, upregulation of defence‐related genes, and changes in metabolic profiles (Mastouri et al ., 2010; Contreras‐Cornejo et al ., 2011; Carreras‐Villasenor et al ., 2012). A recent study showed that Trichoderma harzianum T22 can enhance the production of volatile organic compounds (VOCs) in tomato leading to an increased attractiveness towards aphid parasitoids (Coppola et al ., 2017). A similar study showed that T. atroviride triggers maize defences against the insect herbivore S. frugiperda by the increased emission of volatile terpenes and accumulation of jasmonic acid (JA) (Contreras‐Cornejo et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Coppola et al . () bring another compelling evidence whereby Trichoderma hazarnium , a fungal root symbiont commonly used in biological control, reinforces parasitoid attraction towards aphid‐infested tomato plants. Interestingly, plants infested by aphids and associated with Trichoderma showed enhanced production and release of volatiles known to attract parasitoids, which very likely accounted for observed differences in flight behavior.…”
Section: Direct and Indirect Effects Of Soil Microbial Communities Onmentioning
confidence: 99%
“…Another important challenge is that in the real world these beneficial microbes function in a whole (rhizosphere/phyllosphere) community (i.e., phytobiome), urging a shift toward studies that can shed light on how the effectiveness of these microbes in enhancing pest resistance is modulated in a community context (Lachaise et al, 2017). A fascinating emerging direction of research is the role of microbially produced and induced volatile organic compounds (VOCs) in plant-insect interactions (Rasmann et al, 2017), that can both deter herbivores (Sword et al, 2017) and attract their natural enemies (Coppola et al, 2017). They also play a crucial role in more complex plant-microbe-insect vector interactions.…”
Section: Concluding Remarks and Future Directions For Research On Plamentioning
confidence: 99%